Rethinking the political economy of rural struggles in Turkey: : Space, structures and altered agencies - Kavak, Sinem (Journal of Agrarian Change, 2021)
By focusing on recent water struggles in rural Turkey against run‐of‐the‐river hydropower plants (SHPs), the research delves into the societal and economic factors that enable or inhibit the emergence of strong mobilizations through a comparison of four localities of the Eastern Black Sea region. The main aim of the cross comparison is to determine whether there is a relationship between the forms of rural livelihood (and class position) and political mobilization against SHP construction. The article offers a multilayered relational framework to analyse rural mobilizations. Through a comparative spatial analysis of material and immaterial territories, I argue that the spatio‐economic transformation of the localities that unevenly transform rural settings in terms of production and consumption activities have an impact on the patterns, discourses, and agency in contemporary “rural” mobilizations. This is especially observable with regard to upward mobility and the middle‐classization processes embedded in crop system and household accumulation opportunities. The children of upwardly mobile farmers who became city‐based middle‐class actors tend to present an estheticized and carnivalesque framing in their resistance strategies through the re‐invention of traditions and culture, whereas the lower‐class peasants voice their grievances based strictly on material concerns.
Keywords: material territories; immaterial territories; middle-class activism; rural mobilization; rural space; water struggles